2023
DOI: 10.1038/s41598-023-38209-3
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between femoral lateralization and neck-shaft angle is a joint event after intramedullary nailing of per trochanteric fractures

Abstract: This study explored the relationship between femoral lateralization and femoral neck-shaft angle after intramedullary nail (IM) fixation for per trochanteric fractures. 70 patients (AO/OTA 31A1-2) were investigated. Anteroposterior (AP) and lateral X-ray views pre- and post-operation were recorded. Patients were classified into three groups according to the position of the medial cortex of the head-neck fragment to that of the femoral shaft: being slightly superomedial (positive medial cortex support, PMCS), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…However, when compared with more critical outcomes such as screw cut-out, morbidity, and mortality, the clinical importance of these differences was relatively modest. Cho et al 35 and Fang et al 18 reported similar results. Furthermore, in a retrospective review of 92 patients, Kristan et al 19 and Li et al 20 found that 16 (35%) of 46 patients with intraoperative neutral MCS transitioned to negative MCS at the 6-month postoperative follow-up, whereas this occurrence was found in only 2 (9%) of 23 patients with intraoperative positive MCS (p = 0.022).…”
Section: Which Type Of Amcs Is the Best?mentioning
confidence: 57%
See 1 more Smart Citation
“…However, when compared with more critical outcomes such as screw cut-out, morbidity, and mortality, the clinical importance of these differences was relatively modest. Cho et al 35 and Fang et al 18 reported similar results. Furthermore, in a retrospective review of 92 patients, Kristan et al 19 and Li et al 20 found that 16 (35%) of 46 patients with intraoperative neutral MCS transitioned to negative MCS at the 6-month postoperative follow-up, whereas this occurrence was found in only 2 (9%) of 23 patients with intraoperative positive MCS (p = 0.022).…”
Section: Which Type Of Amcs Is the Best?mentioning
confidence: 57%
“…However, on a global scale, there exists some ambiguity with regard to the precise definition and application of the AMCS types, such as the misidentification of negative reduction as neutral reduction 17 . Moreover, increasing evidence has raised uncertainty with regard to the effectiveness of neutral medial cortical support (MCS), an aspect that has been previously overlooked 18-20 . Therefore, this article aims to distill the AMCS concept from definition to application.…”
mentioning
confidence: 99%